Enhancing Financial Capability and Inclusion in Senegal : A Demand-Side Survey - Zottel, Siegfried; Zia, Bilal; Khoury, Fares (World Bank, Washington, DC, 2016)
Financial capability, as defined by the World Bank and in this report, is the capacity to act in one’s best financial interest, given socioeconomic and environmental conditions. It encompasses knowledge (literacy), attitudes, skills and behavior of consumers with respect to understanding, selecting, and using financial services, and the ability to access financial services that fit their needs (World Bank 2013d). Financial capability has become a policy priority for policy makers seeking to promote beneficial financial inclusion and to ensure financial stability and functioning financial markets. Today people are required to take increasing responsibility for managing a variety of risks over the life cycle. People who make sound financial decisions and who effectively interact with financial service providers are more likely to achieve their financial goals, hedge against financial and economic risks, improve their household’s welfare, and support economic growth. Boosting financial capability has therefore emerged as a policy objective that complements governments’ financial inclusion and consumer protection agendas. To this end, policy makers are increasingly using surveys as diagnostic tools to identify financial capability areas that need improvement and vulnerable segments of the population which could be targeted with specific interventions. The key findings and recommendations presented in this report cover three main areas: financial inclusion, financial capability, and financial consumer protection. The remaining chapters are structured as follows. Chapter one explores the financial inclusion landscape in Senegal. Chapter two gives an overview of Senegalese levels of financial capability, in particular about their financial knowledge, attitudes, and behaviors. Chapter three explores the relationship between financial inclusion and financial capability. The last chapter investigates if the products which financially included individuals use are effectively meeting their needs.